1995
DOI: 10.1161/01.hyp.26.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Alterations in Hypertensive Obese Rabbits

Abstract: There is little information on changes in overall and regional hemodynamics in obesity-associated hypertension. Therefore, the purpose of this study was to determine alterations in overall and regional blood flows and resistances in adipose and nonadipose tissues in a new model of obesity-associated hypertension in rabbits. Sixteen female New Zealand White rabbits were fed either a maintenance or high-fat diet; after 8 to 12 weeks cardiac output and regional blood flows were measured with the use of radioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 28 publications
4
47
0
2
Order By: Relevance
“…In contrast, hydralazine is commonly used as monotherapy in animal studies, but its side effects are often not reported. As some of the potential side effects of hydralazine (eg, tachycardia, RAS activation, and plasma volume expansion) are already exhibited in obesity, 9,23,24 we documented whether the use of hydralazine as antihypertensive therapy exacerbated these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, hydralazine is commonly used as monotherapy in animal studies, but its side effects are often not reported. As some of the potential side effects of hydralazine (eg, tachycardia, RAS activation, and plasma volume expansion) are already exhibited in obesity, 9,23,24 we documented whether the use of hydralazine as antihypertensive therapy exacerbated these effects.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,15,16 Use of hydralazine as antihypertensive therapy in an obesity-hypertension model is further complicated by the fact that potential side effects are similar to physiological changes often seen in obesity (e.g., tachycardia and activation of the reninangiotensin system (RAS)). 9,23,24 Therefore, the purposes of this study were two-fold. First, using the rabbit model, we sought to determine whether the use of hydralazine as an antihypertensive therapy would exacerbate cardiovascular and hormonal alterations already present in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in both fat and organ masses raises whole-body metabolic demands and thus regional blood flows. 3 In turn, cardiac output, the sum of all regional blood flows, increases ( þ 37% in obese rabbits), putting an additional work load on the heart. Although experimental models of high-output heart failure, following the opening of an arteriovenous fistula for example, usually require larger increases in cardiac output (two-to three-fold increase) for heart failure to develop, the contributing load of a moderately increased cardiac output, however, cannot be excluded.…”
Section: Ectopic Fat Storage In the Heartmentioning
confidence: 99%
“…In the last few years, [3][4][5][6][7][8] a new animal model of obesity, the rabbit fed a high-fat diet has allowed us to study many of the mechanisms of obesity-associated cardiovascular pathologies. Ad libitum access to high-fat diet for 8-12 weeks led to a more than three-fold increase in percent fat content determined by carcass analysis and lipid extraction, from 10% in lean rabbits to about 34% in obese rabbits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation